2014
DOI: 10.1002/dta.1767
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of drug intake during pregnancy by questionnaires and LC‐MS/MS drug urine screening: evaluation of both monitoring methods

Abstract: Various studies pointed towards a relationship between chronic diseases such as asthma and allergy and environmental risk factors, which are one aspect of the so-called Exposome. These environmental risk factors include also the intake of drugs. One critical step in human development is the prenatal period, in which exposures might have critical impact on the child's health outcome. Thereby, the health effects of drugs taken during gestation are discussed controversially with regard to newborns' disease risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
(104 reference statements)
1
24
0
Order By: Relevance
“…However, there are a number of recognized agents which can cause false positive results (Moeller et al, 2008), and a MS method is recommended to confirm presence of a drug after a positive result from immunoassay. A screening study by Hoeke et al (2015) compared the results of questionnaires to an untargeted LC-MS/MS urine screen. The authors observed very low agreement between self-reported results and urine screens, between 19 and 25% (Hoeke et al, 2015).…”
Section: Types Of Screening For Illicit Drugs In Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a number of recognized agents which can cause false positive results (Moeller et al, 2008), and a MS method is recommended to confirm presence of a drug after a positive result from immunoassay. A screening study by Hoeke et al (2015) compared the results of questionnaires to an untargeted LC-MS/MS urine screen. The authors observed very low agreement between self-reported results and urine screens, between 19 and 25% (Hoeke et al, 2015).…”
Section: Types Of Screening For Illicit Drugs In Pregnant Womenmentioning
confidence: 99%
“…A screening study by Hoeke et al (2015) compared the results of questionnaires to an untargeted LC-MS/MS urine screen. The authors observed very low agreement between self-reported results and urine screens, between 19 and 25% (Hoeke et al, 2015). In another study, urine samples were collected from neonates suspected to have been exposed to illicit drugs (Hon et al, 2016).…”
Section: Types Of Screening For Illicit Drugs In Pregnant Womenmentioning
confidence: 99%
“…Antibacterial therapy during gestation or lactation was mainly performed by penicillin, macrolide, and lincosamide antibiotics, although low detection numbers were observed for these drugs, according to the study design and the dosing. However, as shown in a previous work using the identical 36th WOP samples and corresponding questionnaires, there is a huge discrepancy between reporting and detection of antibiotics in this setup . Antihypertensive therapy was guideline orientated using methyldopa or beta‐blockers instead of, for example, Ca 2+ ‐antagonists or ACE‐inhibitors during pregnancy or lactation …”
Section: Discussionmentioning
confidence: 96%
“…This method provides the most comprehensive LC–MS urine screening, which is available . However, to obtain the best information on drug utilization, a combined usage of all mentioned methods should be used …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation